Distinct neurexin isoforms cooperate to initiate and maintain foraging activity - Brandon L. Bastien; Mara H. Cowen; Michael P. Hart (Translational Psychiatry, 2023)
Abstract Neurexins are synaptic adhesion molecules that play diverse roles in synaptic development, function, maintenance, and plasticity. Neurexin genes have been associated with changes in human behavior, where variants in NRXN1 are associated with autism, schizophrenia, and Tourette syndrome. While NRXN1, NRXN2, and NRXN3 all encode major α and β isoforms, NRXN1 uniquely encodes a γ isoform, for which mechanistic roles in behavior have yet to be defined. Here, we show that both α and γ isoforms of neurexin/nrx-1 are required for the C. elegans behavioral response to food deprivation, a sustained period of hyperactivity upon food loss. We find that the γ isoform regulates initiation and the α isoform regulates maintenance of the behavioral response to food deprivation, demonstrating cooperative function of multiple nrx-1 isoforms in regulating a sustained behavior. The γ isoform alters monoamine signaling via octopamine, relies on specific expression of NRX-1 isoforms throughout the relevant circuit, and is independent of neuroligin/nlg-1, the canonical trans-synaptic partner of nrx-1. The α isoform regulates the pre-synaptic structure of the octopamine producing RIC neuron and its maintenance role is conditional on neuroligin/nlg-1. Collectively, these results demonstrate that neurexin isoforms can have separate behavioral roles and act cooperatively across neuronal circuits to modify behavior, highlighting the need to directly analyze and consider all isoforms when defining the contribution of neurexins to behavior.